Tuning the Thermal Stability and Photoisomerization of Azoheteroarenes through Macrocycle Strain - Vela, Sergi (John Wiley and Sons Inc., 2020)

(untitled) (Chemistry)
Azobenzene and its derivatives are one of the most widespread molecular scaffolds used in a range of modern applications, as well as in fundamental research. After photoexcitation, azo‐based photoswitches revert back to the most stable isomer on a timescale ([Formula: see text] ) that determines the range of potential applications. Attempts to bring [Formula: see text] to extreme values prompted the development of azobenzene and azoheteroarene derivatives that either rebalance the E‐ and Z‐isomer stabilities, or exploit unconventional thermal isomerization mechanisms. In the former case, one successful strategy has been the creation of macrocycle strain, which tends to impact the E/Z stability asymmetrically, and thus significantly modify [Formula: see text] . On the bright side, bridged derivatives have shown an improved optical switching owing to the higher quantum yields and absence of degradation. However, in most (if not all) cases, bridged derivatives display a reversed thermal stability (more stable Z‐isomer), and smaller [Formula: see text] than the acyclic counterparts, which restricts their potential interest to applications requiring a fast forward and backwards switch. In this paper, the impact of alkyl bridges on the thermal stability of phenyl‐azoheteroarenes is investigated by using computational methods, and it is revealed that it is indeed possible to combine such improved photoswitching characteristics while preserving the regular thermal stability (more stable E‐isomer), and increased [Formula: see text] values under the appropriate connectivity and bridge length.